Method for preparing a coated paper product
Patent Information
- Application Number
- CN202280045109.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-07-26
- Filing Date
- 2022-06-21
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2042-06-21
AI Technical Summary
然而,PVAc不能提供包装应用所需的良好阻隔性能
[0007]本发明可用于制备具有耐油脂性、矿物油阻隔性能和热封性的制品。
Smart Images

Figure BDA0004625936330000021 
Figure BDA0004625936330000071 
Figure BDA0004625936330000081
Abstract
Description
Background Technology
[0001] This invention relates to a method for preparing coated paper articles, and more specifically, a method for preparing paper or paperboard coated with partially hydrolyzed poly(vinyl ester-co-acrylate). Due to the renewable and biodegradable nature of paper, paper and paperboard are increasingly used in packaging applications as sustainable alternatives to plastic packaging. In many applications, paper and paperboard require a barrier coating to reduce the permeation of oils, greases, moisture, and oxygen through these substrates. Achieving oil resistance (OGR) is crucial for paper and paperboard packaging used in food service applications, such as sandwich wraps, popcorn bags, and bread boxes. Barrier coatings designed for these applications typically prevent oil from seeping into the underlying paper substrate, which can alter the appearance of the material and reduce the structural integrity of the packaging.
[0002] Conventional OGR paper is treated with perfluorocarbon additives, which, despite being highly effective barrier materials, are subject to stringent regulatory scrutiny. Extruded plastic films (such as polyethylene) have also been used to coat paper and paperboard and have been found to exhibit good barrier properties. However, extrusion coating requires off-machine application and produces unnecessarily thick films, increasing costs and limiting the repulping and recyclability of these coated paper products.
[0003] Aqueous dispersion coatings are environmentally friendly alternatives to fluorinated compounds and polyethylene coatings, and they can be applied at low coating weights to improve the repulping and recyclability of paper packaging. Synthetic latexes based on acrylic, styrene-acrylic (SA), and styrene-butadiene (SB) polymers are the most commonly used materials in barrier coating applications. These compositions can provide excellent OGR for paper and paperboard substrates, but often lack other coating properties important for the production and application of paper products, such as flexibility (or foldability), anti-tack properties, and heat-sealing properties. Poly(vinyl acetate) (PVAc) dispersions are a class of synthetic latexes traditionally used in coating compositions in the paper industry. These latexes offer advantages over SA and SB type adhesives, such as low cost, thermal and light stability, adhesiveness, and anti-foaming properties. However, PVAc does not provide the good barrier properties required for packaging applications. Therefore, developing cost-effective and environmentally friendly products with acceptable grease resistance and barrier properties would be a significant advancement in the field of coated paper and paperboard products. Summary of the Invention
[0004] This invention addresses a need in the art by providing a method comprising the steps of: applying a composition to a paper or cardboard substrate, and then drying the composition to form a substrate overlapping a film, the film having a content of 1 g / m³. 2 Up to 20g / m 2Dry coating weight within the specified range;
[0005] The composition comprises an aqueous dispersion of copolymer particles, which, based on the weight of the copolymer particles, comprises: a) 40% to 96% by weight of vinyl ester structural units; b) 2% to 50% by weight of vinyl alcohol structural units; and c) 0.5% to 30% by weight of C1-C8 linear or branched alkyl acrylate monomer structural units.
[0006] The aqueous dispersion has a solids content in the range of 15% to 60% by weight; and at least 50% by weight of the membrane comprises one or more polymers, wherein at least 50% by weight of the one or more polymers comprises structural units of vinyl ester, vinyl alcohol and acrylate monomers.
[0007] This invention can be used to prepare products with oil resistance, mineral oil barrier properties, and heat-sealing properties. Detailed Implementation
[0008] This invention is a method comprising the steps of: applying a composition to a paper substrate or cardboard substrate, and then drying the composition to form a substrate overlapping a film, the film having a content of 1 g / m³. 2 Up to 20g / m 2 Dry coating weight within the range;
[0009] The composition comprises an aqueous dispersion of copolymer particles, which, based on the weight of the copolymer particles, comprises: a) 40% to 96% by weight of vinyl ester structural units; b) 2% to 50% by weight of vinyl alcohol structural units; and c) 0.5% to 30% by weight of C1-C8 linear or branched alkyl acrylate monomer structural units.
[0010] The aqueous dispersion has a solids content in the range of 15% to 60% by weight; and at least 50% by weight of the membrane comprises one or more polymers, wherein at least 50% by weight of the one or more polymers comprises structural units of vinyl ester, vinyl alcohol and acrylate monomers.
[0011] As used herein, the term "structural unit" for a monomer refers to the residue of the monomer after polymerization. For example, the structural unit of vinyl alcohol is shown below:
[0012]
[0013] The dashed lines represent the connection points between the structural units and the polymer backbone.
[0014] The composition for preparing coated paper or paperboard substrates is advantageously prepared in two steps: in the first step, vinyl esters and C1-C8 linear or branched alkyl acrylates are copolymerized under emulsion polymerization conditions to form a dispersion of poly(vinyl ester-co-acrylate) copolymer particles; then, the copolymer is partially hydrolyzed with an alkali to form a dispersion of polymer particles comprising structural units of vinyl ester, vinyl alcohol, and acrylate. Therefore, the vinyl alcohol structural units do not require the use of vinyl alcohol as a starting material.
[0015] Other monomers that can be used in the polymerization reaction include carboxylic acid monomers and sulfonic acid monomers or their salts. Examples of suitable carboxylic acid monomers include acrylic acid, methacrylic acid, fumaric acid, itaconic acid, crotonic acid, and maleic acid; examples of suitable sulfonic acid monomers include ethyl methacrylate, ethyl methacrylate, propyl methacrylate, propyl methacrylate, vinyl sulfonic acid, 2-acrylamido-2-methylpropanesulfonic acid, and 2-methacrylamido-2-methylpropanesulfonic acid, and their salts. Based on the weight of the polymer particles, the concentration of the structural units of the carboxylic acid monomers is typically in the range of 0.1 wt% to 5 wt%; based on the weight of the polymer particles, the concentration of the structural units of the sulfonic acid monomers is typically in the range of 0.1 wt% to 5 wt%.
[0016] Based on the weight of the monomer, polyene-bonded unsaturated monomers can also typically be used in polymerization reactions at concentrations ranging from 0.1% to 5% by weight. Examples of suitable polyene-bonded unsaturated monomers include allyl methacrylate, ethylene glycol dimethacrylate, diallyl maleate, and diallyl phthalate.
[0017] As used herein, the term "acrylate monomer" refers to acrylate or methacrylate monomers. Suitable C1-C8 linear or branched alkyl acrylate monomers (alkyl acrylate monomers) include methyl acrylate, methyl methacrylate, ethyl acrylate, n-butyl acrylate, n-butyl methacrylate, isobutyl acrylate, tert-butyl acrylate, and 2-ethylhexyl acrylate.
[0018] Examples of vinyl esters include vinyl acetate, vinyl propionate, vinyl butyrate, vinyl octanoate, vinyl lauryl acetate, and vinyl tert-carbonate, with vinyl acetate being preferred. Based on the weight of the polymer particles, the concentration of the vinyl ester structural units in the composition used to prepare the coated substrate ranges from 40 wt% to 96 wt%; based on the weight of the polymer particles, the concentration of the vinyl alcohol structural units ranges from 2 wt% or 5 wt% or 8 wt% to 50 wt% or up to 40 wt%. The concentration of the alkyl acrylate monomer structural units ranges from 0.5 wt% or 1 wt% to 30 wt% or up to 25 wt%, but it has been found that a narrower range at higher concentrations of vinyl alcohol structural units is optimal; more particularly, when the concentration of vinyl alcohol structural units ranges from 13 wt% or 20 wt% to 40 wt%, the concentration of the alkyl acrylate monomer structural units ranges from 3 wt% or 4 wt% to 20 wt%.
[0019] When a composition for manufacturing a coated substrate is prepared by hydrolyzing a copolymer of vinyl ester and acrylate monomers under alkaline conditions, the composition further comprises a carboxylate formed as a hydrolysis byproduct. This salt can be removed from the composition if desired. When the vinyl ester is vinyl acetate, the composition may contain acetate anions at concentrations ranging from 5% or 8% to 40% or 35% by weight, based on the weight of the acetate anion and the structural units of vinyl acetate, vinyl alcohol, and acrylate monomers. Sodium acetate, potassium acetate, and ammonium acetate are examples of acetates, with sodium acetate being the most common.
[0020] The composition used to prepare the coated substrate may include additional materials such as surfactants, adhesives, waxes, defoamers, dispersants, rheology modifiers, pigments, crosslinking agents, and colorants. Although optical brighteners may be included in the compositions used in the methods of the present invention, it is preferable to avoid using such agents because the final application of the prepared coated paper or paperboard is most commonly in the food packaging field. Therefore, based on the weight of the composition, the concentration of optical brighteners is preferably less than 5% by weight, more preferably less than 1% by weight, and most preferably 0% by weight.
[0021] The article of the present invention is advantageously prepared by the following steps: applying an aqueous composition to a paper or paperboard substrate in an amount sufficient to achieve the desired coating weight, and then drying the composition at a high temperature until water is removed. The film comprises one or more polymers, wherein, based on the weight of the film, at least 50 wt%, or at least 65 wt%, or at least 75 wt%, or at least 85 wt%, or at least 95 wt% of one or more polymers comprises copolymers of vinyl ester, vinyl alcohol, and acrylate monomers. The coating may comprise other polymers, such as acrylic acid, styrene-butadiene, and styrene-acrylic acid polymers. Alternatively, based on the weight of the acetate anion and preferably the structural units of vinyl acetate, vinyl alcohol, and acrylate monomers, the coating comprises 60 wt% or 65 wt% to 95 wt% or to 92 wt% of the structural units of preferably vinyl acetate, vinyl alcohol, and acrylate monomers and 5 wt% or 8 wt% to 40 wt% or to 30 wt% of acetate anions. The method of the present invention provides coated paper or paperboard substrates with excellent oil and grease barrier properties.
[0022] Example
[0023] Intermediate Example 1 – Preparation of Vinyl Acetate-Butyl Acrylate Latex
[0024] Deionized water (783.0 g) was placed in a 5 L, 4-necked round-bottom flask and heated to 60 °C under N2. In a separate container, a mixture containing deionized water (451.0 g), sodium vinyl sulfonate (32.0 g, 25% aqueous solution), sodium acetate (4.0 g), and TERGITOL was prepared. TMA monomer emulsion of 15-S-40 surfactant (trademark of The Dow Chemical Company or its affiliates, 22.9 g, 70% aqueous solution), Disponil FES 993 emulsifier (106.6 g, 30% aqueous solution), glacial acrylic acid (8.0 g), butyl acrylate (32.0 g), and vinyl acetate (1552.0 g). A portion of the monomer emulsion (44.2 g) was added to the reactor and rinsed (16.0 g water), followed by the addition of ammonium persulfate (1.5 g dissolved in 8.0 g water) and rinsed (8.0 g water), then a solution of sodium bisulfite (0.3 g), ferrous sulfate heptahydrate (17 mg), and sodium dithionite (0.6 g) in 8.0 g water was added and rinsed (8.0 g water). After holding for 2 minutes, the remaining portion of the monomer emulsion was fed into the reactor over 120 minutes. A solution of ammonium persulfate (4.9 g) and tert-butyl hydroperoxide (2.0 g) in 120.0 g of water, along with a sodium bisulfite solution (3.2 g dissolved in 120.0 g of water), was simultaneously added to the reactor over 130 minutes at a temperature ranging from 64°C to 66°C. After all feeds and rinsing were completed, the reactor was cooled to 60°C, and then a solution of ammonium persulfate (0.5 g) and tert-butyl hydroperoxide (1.7 g) in 48.0 g of water, along with a sodium bisulfite solution (2.7 g dissolved in 48.0 g of water), was simultaneously fed over 30 minutes. The reactor was then cooled to room temperature, and ammonium hydroxide (6.9 g, 28 wt%) was added dropwise to raise the pH to 6.5 to 7.5. The solids content was found to be 48 wt%.
[0025] Intermediate Example 2 – Partial Hydrolysis of a Copolymer of Vinyl Acetate and Butyl Acrylate
[0026] At room temperature, a portion of intermediate 1 latex (300 g, approximately 48% solids) was placed in a wide-mouth flask, and then sodium hydroxide solution (10% by weight aqueous solution) was added dropwise to the stirred latex over 1 hour to reach the target hydrolysis level. The partially hydrolyzed latex had a pH ranging from 9.0 to 10.0, and solids ranging from 27% to 46%, depending on the degree of hydrolysis. The sample was stored at room temperature, and the degree of hydrolysis was determined by HPLC analysis of acetic acid produced via the cleavage of acetate groups, as described in the following sections.
[0027] High-performance liquid chromatography (HPLC) analysis of acetic acid
[0028] HPLC analysis was performed using an Agilent 1100 series HPLC system equipped with a Phenomenex Rezex ROA Organic Acid H+ 240 mm × 4.6 mm column (8 μm particle size, 8% crosslinked sulfonated styrene-divinylbenzene), a Phenomenex Carbo-H4 column guard, and a UV detector operating at 210 nm. The hydrolyzed latex sample was diluted tenfold and centrifuged at 100,000 rpm for 15 min, followed by filtration of the supernatant through a 0.45 μm PVDF syringe filter. Sample injection volume was 5 μL, and separation was performed using 2.5 mM phosphoric acid at a flow rate of 0.4 mL / min and a column temperature of 35 °C. The instrument was externally calibrated using acetic acid from 50 ppm to 10,000 ppm.
[0029] The stability of the hydrolyzed latex was evaluated and is shown in Table 1. The weight percentages of the structural units of vinyl acetate (VA), butyl acrylate (BA), and vinyl alcohol are based on the weight of the polymer, and the weight percentage of acetate anion (AcO-) is based on the weight of the total solids of the hydrolyzed copolymer and AcO-. Samples that remained uncured after 6 months passed the stability test, while samples that cured within 3 months failed the test.
[0030] Table 1 – Stability of Partially Hydrolyzed Polyvinyl Acetate Latex
[0031] Comparative Example 1 0 87.7 11.2 13.1 Unqualified Comparative Example 2 10 89 0 0 qualified Example 1 2.2 85.7 11.0 12.8 qualified Example 2 6.6 81.8 10.5 12.3 qualified Example 3 7.3 68.2 23.3 23.8 qualified Example 4 11.0 78.0 10.0 11.8 qualified Example 5 12.1 64.6 22.0 22.8 qualified Example 6 13.5 48.2 37.0 33.1 qualified Example 7 21.7 68.5 8.8 10.5 qualified
[0032] Data demonstrates the importance of acrylates in achieving latex stability.
[0033] Preparation of coated substrate
[0034] Examples 1 to 7: Latex was applied longitudinally to UPM Brilliant Pro paper (basic weight: 62 g / m²) using an automatic coating machine (K-controlled coating machine) equipped with various winding bars. 2 To achieve 5g / m 2 ±0.3g / m 2 The dry coating weight. Dry the sample at 100°C for 2 minutes. According to TAPPI 402 standard, conditioned the coated paper in a temperature-controlled chamber for at least 1 hour.
[0035] 3M reagent kit test
[0036] The grease resistance of coated paper samples was tested using the TAPPI method T559-cm-12 with an extended range of kit scores. A kit solution composed of castor oil, toluene, and heptane in varying proportions was applied dropwise to the coated substrate, allowed to stand for 15 seconds, and then wiped off. Any occurrence of solvent penetration or substrate discoloration was classified as a failure for this kit solution. The kit score for a given sample was assigned using the number of the highest (most aggressive) kit solution passed through the coated substrate. In the TAPPI method, the kit score ranges from 1 to 12 for the composition of the kit solution. Alternatively, more aggressive solutions were prepared to assign kit values up to 16, as shown in Table 2 below. Each sample was tested in duplicate.
[0037] Table 2 – Reagent Tests
[0038]
[0039] Hexane vapor transmission rate (HVTR)
[0040] Before conducting the experiment, condition the coated paper sample overnight in a fume hood. Cut the coated paper substrate into 2.5-inch circles. Use a pipette to place reagent-grade n-hexane (5 g) into a permeation cup. Place the sample-coated side down on top of the rubber gasket and tighten the cap to clamp the sample onto the permeation cup. Record the initial mass of the permeation cup with the sample attached and weigh the cup again after 24 hours. To calculate the hexane vapor permeability, subtract the weight after 24 hours from the initial weight and then divide by 0.000212 (the area of the exposed sample). This calculation provides the result in g / m². 2 . Hexane vapor permeability measured in days.
[0041] heat sealability
[0042] The ability to heat-seal coated paper was evaluated using a single-phase Sentinel laboratory heat sealer. Coated samples were cut into 2-inch × 4-inch rectangles, and the coated side was placed in the heat sealer's clamp for 0.5 seconds at 190°C and 100 psi. After the substrate was cooled to room temperature, the two sheets were separated. Samples that separated with fiber tearing were considered acceptable, while those that separated without fiber tearing were considered unacceptable. Two copies of the samples were tested. Table 3 shows the barrier properties of various coatings.
[0043] Table 3 – Barrier Properties of Polyvinyl Acetate Latex
[0044]
[0045] Data show that coatings prepared from partially hydrolyzed copolymers have improved grease resistance, mineral oil barrier properties (lower HVTR), and heat-sealing properties compared to coatings prepared from unhydrolyzed latex compositions.
Claims
1. A method comprising the following steps: The composition is applied to a paper or cardboard substrate, and then the composition is dried to form a substrate that overlaps with a film having a concentration of 1 g / m³. 2 Up to 20g / m 2 The weight of the dry coating within the specified range; The composition comprises an aqueous dispersion of copolymer particles, the aqueous dispersion comprising, based on the weight of the copolymer particles: a) 40% to 96% by weight of vinyl ester structural units; b) 2% to 50% by weight of vinyl alcohol structural units; c) 0.5% to 30% by weight of C1-C8 linear or branched alkyl acrylate monomer structural units; optionally, carboxylic acid monomers and sulfonic acid monomers or salts thereof; And optional polyene-bonded unsaturated monomers; The aqueous dispersion has a solids content in the range of 15% to 60% by weight; and at least 50% by weight of the membrane comprises one or more polymers, wherein at least 85% by weight of the one or more polymers comprises structural units of vinyl ester, vinyl alcohol and the acrylate monomer.
2. The method according to claim 1, wherein the C1-C8 linear or branched alkyl acrylate monomer is selected from the group consisting of: methyl acrylate, methyl methacrylate, ethyl acrylate, n-butyl acrylate, n-butyl methacrylate, isobutyl acrylate, tert-butyl acrylate, and 2-ethylhexyl acrylate; and the vinyl ester is vinyl acetate.
3. The method of claim 2, wherein, based on the weight of the copolymer particles, the copolymer particles comprise: 8% to 50% by weight of vinyl alcohol structural units; and 1% to 25% by weight of the structural units of the C1-C8 linear or branched alkyl acrylate monomer.
4. The method according to claim 2, wherein when the concentration of the structural unit of the vinyl alcohol is in the range of 13% to 40% by weight, the concentration of the structural unit of the C1-C8 linear or branched alkyl acrylate monomer is in the range of 3% to 20% by weight.
5. The method according to claim 3, wherein the C1-C8 linear or branched alkyl acrylate monomer is n-butyl acrylate.
6. The method according to any one of claims 2 to 5, wherein at least 85% by weight of the one or more polymers comprises structural units of vinyl acetate, vinyl alcohol, and the C1-C8 linear or branched alkyl acrylate monomer.
7. The method of claim 2, wherein the composition comprises: a) 60% to 95% by weight of the structural unit of vinyl acetate, vinyl alcohol, and the C1-C8 linear or branched alkyl acrylate monomer; and b) 5% to 40% by weight of acetate anion; wherein the weight percentage range is based on the weight of the acetate anion and the structural unit of vinyl acetate, vinyl alcohol, and the C1-C8 linear or branched alkyl acrylate monomer.
8. The method according to any one of claims 4 or 7, wherein the C1-C8 linear or branched alkyl acrylate monomer is n-butyl acrylate.
9. The method of claim 1, wherein the composition further comprises at least one additional material selected from the group consisting of: surfactants, binders, defoamers, waxes, dispersants, rheology modifiers, pigments, crosslinking agents, and colorants; and less than 5% by weight of a fluorescent whitening agent based on the weight of the composition.
10. The method of claim 1, wherein the composition further comprises less than 1% by weight of a fluorescent whitening agent based on the weight of the polymer particles.
Citation Information
Patent Citations
Organofunctional silicone copolymers and the saponification products thereof
CN1646607A
Greaseproof paper having excellent folding resistance
US20150259856A1